2018
DOI: 10.1016/j.neulet.2018.06.014
|View full text |Cite
|
Sign up to set email alerts
|

N-acetylcysteine prevents ketamine-induced adverse effects on development, heart rate and monoaminergic neurons in zebrafish

Abstract: N-acetylcysteine, a precursor molecule of glutathione, is an antioxidant. Ketamine, a pediatric anesthetic, has been implicated in cardiotoxicity and neurotoxicity including modulation of monoaminergic systems in mammals and zebrafish. Here, we show that N-acetylcysteine prevents ketamine’s adverse effects on development and monoaminergic neurons in zebrafish embryos. The effects of ketamine and N-acetylcysteine alone or in combination were measured on the heart rate, body length, brain serotonergic neurons an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 38 publications
0
11
0
Order By: Relevance
“…Also, in this study, histopathological examinations showed the reduction of mononuclear cells infiltration in treated rats with NAC (Figure ). Previous studies reported that NAC can react with OH radicals and keep tissues from injuries due to the formation of glutathione in the cells and preventing the reduction of antioxidant enzyme activities (Ahmad et al, ; Grisanti et al, ; Robinson, Dumas, Gu, & Kanungo, ). Increased SOD and CAT activities and improved kidney histopathological changes in NAC‐treated group may be resulted from, at least partly, NAC antioxidant activity (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…Also, in this study, histopathological examinations showed the reduction of mononuclear cells infiltration in treated rats with NAC (Figure ). Previous studies reported that NAC can react with OH radicals and keep tissues from injuries due to the formation of glutathione in the cells and preventing the reduction of antioxidant enzyme activities (Ahmad et al, ; Grisanti et al, ; Robinson, Dumas, Gu, & Kanungo, ). Increased SOD and CAT activities and improved kidney histopathological changes in NAC‐treated group may be resulted from, at least partly, NAC antioxidant activity (Figures and ).…”
Section: Discussionmentioning
confidence: 99%
“…First, using 2 m m ketamine and 1 m m ALCAR doses, which we have used in many of our previous studies (Guo et al, ; Kanungo et al, , ; Robinson et al, ; Robinson et al, ; Robinson, Dumas, Ali, et al, ; Robinson, Dumas, Gu, et al, ; Robinson, Gu, Ali, Dumas, & Kanungo, ; Trickler et al, ), we discovered that, in the 28 hpf embryos, 2 m m ketamine with 50 μ m nifedipine was less toxic than 50 μ m nifedipine alone. Surprisingly, embryos treated with 50 μ m nifedipine and 2 m m ketamine showed a better body axis than the embryos treated only with 50 μ m nifedipine.…”
Section: Discussionmentioning
confidence: 88%
“…As our previous studies showed counteracting effects of ALCAR and ketamine (Cuevas et al, ; Guo et al, ; Kanungo et al, ; Robinson et al, ; B. L. Robinson et al, ; B. L. Robinson et al, ), we hypothesized that if ALCAR exacerbates the effect of nifedipine, ketamine would alleviate it. In the presence of 2 m m ketamine in water, which we have used in our previous studies (Guo et al, ; Kanungo et al, ; Kanungo, Cuevas, Ali, & Paule, ; Robinson, Dumas, Gu, et al, ; B. L. Robinson et al, ; Robinson, Dumas, Ali, et al, ; B. L. Robinson et al, ; Trickler et al, ) that gives an internal dose of ~8.4 μ m in the zebrafish embryos (Trickler et al, ), nifedipine toxicity appeared to be milder (Figure ). Nifedipine‐induced axial curvature was no more apparent in ketamine and nifedipine co‐treated embryos (Figure ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations